2017
DOI: 10.1002/bin.1513
|View full text |Cite
|
Sign up to set email alerts
|

Exchange‐based communication training may not consistently facilitate communication in the absence of the requested item

Abstract: The role of stimulus presence on spontaneous communication was assessed with 3 participants in a nonconcurrent multiple baseline with embedded reversals design. Participants were taught to request 2 highly preferred items. Once mastery criterion was met, test sessions were conducted with stimuli either visible or absent from the room, and request rate was measured. For 2 participants, training produced requests in both the presence and absence of the stimulus. For one participant, however, the presence of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
1
0
0
Order By: Relevance
“…To evaluate if these mands occurred as part of a communicative chain, as well to determine if the other reinforcers were still relevant, we removed bubbles from the pool of available items. When bubbles were removed at session 72, mands for bubbles decreased and mands for Kindle and snacks increased (this particular finding is similar to Pizarro & Borrero, 2017, who found that some clients may not request items in their absence).…”
supporting
confidence: 78%
“…To evaluate if these mands occurred as part of a communicative chain, as well to determine if the other reinforcers were still relevant, we removed bubbles from the pool of available items. When bubbles were removed at session 72, mands for bubbles decreased and mands for Kindle and snacks increased (this particular finding is similar to Pizarro & Borrero, 2017, who found that some clients may not request items in their absence).…”
supporting
confidence: 78%